Development of Practicum Principles Based on Problem Solving for Class VIII Students Semester 1 First Middle School - Reni Resti Pauzi; Fitri Arsih; Ristiono - (ATRIUM PENDIDIKAN BIOLOGI, 2017)
The purpose of  this study is produce a product. There is problem solving,s practical guidance for VIII grade in first term on junior high school. This research is developed   by three stages of 4-D models. They are definiton design and development. This research use 4 validators,  they are 2 lecturers and 2 teachers. The subject of this researchis 20 students at VIII grade at  SMP Pertiwi Padang.  The data are primary data and data of  the result. Result of the test is a developed  product the practical guidance base problem solving, aquired, valid and  practical.